Synthesis and Antimicrobial Activity of New Pyrrolecarboxylic Acid Derivatives of Ampicillin and Amoxicillin - Bijev, Atanas T.; Hung, Vu (Arzneimittelforschung, 2001)
Twelve new penicillin derivatives were prepared for microbiological evaluation by N-acylation of ampicillin (CAS 69-53-4) and amoxicillin (CAS 26787-78-0) with activated pyrrolecarbocylic acids via mixed anhydrides following the Schotten-Baumann procedure. An alternative synthetic approach via chloroanhydrides was checked and rejected because of the instability established for these intermediates. NMR and IR spectral data together with TLC confirmed the structure and the purity of the new products.Antimicrobial tests in vitro indicated a reduction of the antibacterial activity compared with that of ampicillin and amoxicillin as reference antibiotics, but their minimal inhibitory concentrations (MIC) were still in the range of 0.62-16 μg/ml against standard and clinical Gram positive strains. Preliminary toxicological evaluations showed low toxicity.
Keywords: Amoxicillin; Ampicillin; Antibiotics; Penicillins; Pyrroles, antimicrobial activity, synthesis